The Effect of Tri Hita Kirana (Thk) Principles on Improving Psychological Wellbeing and Employee Performance in the Work Environment of STKIP Muhammadiyah Manokwari West Papua - Hasan, Hawa; Made Sutajaya; Wayan Suja (Indonesian Journal Publisher, 2025)
This study aims to analyze the effect of the application of Tri Hita Kirana (THK) values on psychological well-being and employee performance. Based on the results of the analysis using the Partial Least Squares (PLS) method, it was found that the application of THK had a significant influence on both variables. The R Square test results show that the independent variables in the model are able to explain 62.3% of the variation in psychological well-being and 48.7% of the variation in employee performance. The influence of THK on psychological well-being is indicated by a path coefficient value of 0.789 and on employee performance of 0.698, both with significant T-Statistics values (greater than 1.96) and a very low P-value (0.000). In addition, the F Square analysis revealed that THK has a large influence on psychological well-being (f² = 1.653) and employee performance (f² = 0.951). From the PLS and Linear Model (LM) prediction results, the PLS model showed better prediction performance with lower RMSE and MAE values, as well as higher Q²_predict than the LM, indicating better predictive power in the PLS model. This finding confirms the importance of applying THK values in improving the quality of psychological well-being and employee performance in organizations, and shows that the PLS model is more effective in predicting the relationship between variables in this study.